Emotional Intelligence and Internal Marketing as Determinants of Job Satisfaction and Satisfaction with Life among Portuguese Professionals - Serafim, Ana (2024)
The main purpose of this study is to analyze emotional intelligence and internal marketing as predictors of job satisfaction and satisfaction with life among working professionals in Portugal. At the same time, the relationships between internal marketing, job satisfaction, job determinants, organizational commitment, job performance and employee loyalty are explored. To this end, a conceptual model and a set of hypotheses were defined to respond to the postulated research objectives using structural equation modeling, applied to a random sample (n = 1310). The research results show that internal marketing has a statistically significant influence on job satisfaction. In turn, job satisfaction has a direct and positive influence on employee commitment and employee loyalty. Commitment and emotional intelligence have a direct, positive and significant influence on performance. Job satisfaction and emotional intelligence have a positive influence on satisfaction with life. This study presents itself as a novelty for science while making important contributions to organizations since it conceives a new conceptual model that enables organizations to perceive the relationships between the different determinants of job satisfaction and performance in order to promote their productivity, profitability and organizational competitiveness.